Purely Small Submodules and Purely Hollow Modules - Ahmed, Muna Abbas; Dhari, Iman Abdulhadi; Atiya, Zainab Abed (Iraqi Journal of Science, 2022)
The main goal of this paper is to give a new generalizations for two important classes in the category of modules, namely the class of small submodules and the class of hollow modules. They are purely small submodules and purely hollow modules respectively. Various properties of these classes of modules are investigated. The relationship between purely small submodules and P-small submodules which is introduced by Hadi and Ibrahim, is studied. Moreover, another characterization of purely hollow modules is considered.